Digital literacy ability of private vocational students in Surabaya City - Habibi, Mohammad Wildan; Buditjahjanto, I Gede Putu Asto; Rijanto, Tri (Intelektual Pustaka Media Utama, 2024)
Digital literacy is an important part of vocational secondary school education. Along with the development of technology and the expansion of access to digital resources, digital literacy is very important for vocational students. Digital literacy itself indirectly helps Vocational High School students to gain greater access to information and helps them in the learning process of various topics using trusted sources. This descriptive quantitative research aims to analyze the digital literacy skills of private vocational students in Surabaya City. Students' digital literacy ability was measured with the Likert Scale as a variable in this study. The population consists of students from four private vocational schools in Surabaya City with a total of 700 students. The sample consisted of 100 students, using a random sampling technique. Data collection is carried out through digital literacy instruments and data analysis using descriptive analysis. The results of the research data analysis showed that respondents' ability to elements of basic literacy skills averaged 2.79, average background knowledge 2.26, and information and communication technology (ICT) skills averaged 2.53. In addition, the attitudes and views of users of student information averaged 2.59. The results showed that the digital literacy ability of private vocational school students in Surabaya City was in the